1976
DOI: 10.1111/j.1755-3768.1976.tb01263.x
|View full text |Cite
|
Sign up to set email alerts
|

Static Perimetry: Accuracy and Fluctuations

Abstract: Threshold fluctuations are divided into short-term and long-term effects applying statistical methods. Sixteen normal and pathological visual fields were analysed in order to obtain values for the short-term, long-term and total fluctuations. Special attention is paid to fortuitous variations between the results obtained at successive examinations. Finally the concept of spatial correlations is introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1
1

Year Published

1977
1977
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(18 citation statements)
references
References 7 publications
1
15
1
1
Order By: Relevance
“…When introducing probabilities deduced from a frequency-of-seeing curve for untrained subjects (Greve 1973) in computer simulations, the resulting dispersion was found to be close to the mean dispersion obtained in the normal visual fields in this study. The dispersions of this study were of the same magnitude as those found by Bebie et al (1976) and those measured earlier by us (Heijl & Krakau 1975a). The dispersion represents a real variation in the results of the threshold estimation and are not due to a change of the mean threshold -a general constriction or widening of the visual field -between the test sessions.…”
Section: Discussionsupporting
confidence: 78%
“…When introducing probabilities deduced from a frequency-of-seeing curve for untrained subjects (Greve 1973) in computer simulations, the resulting dispersion was found to be close to the mean dispersion obtained in the normal visual fields in this study. The dispersions of this study were of the same magnitude as those found by Bebie et al (1976) and those measured earlier by us (Heijl & Krakau 1975a). The dispersion represents a real variation in the results of the threshold estimation and are not due to a change of the mean threshold -a general constriction or widening of the visual field -between the test sessions.…”
Section: Discussionsupporting
confidence: 78%
“…These define short-term fluctuation (SF) and long-term fluctuation (LF) as the components of variability in automated static perimetry. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Left eye values were inverted to right eye values and the results from both eyes were combined for this report. The components of fluctuation were calculated from a statistical random three-fold nested model according to the number of repetitions nested in locations, nested in sessions, nested in individuals in this study (Bebie et al 1976;Graybill 1961). This model defines four components of fluctuation: The short-term component describes the fluctuation which occurs within a single visual field exam.…”
Section: Methodsmentioning
confidence: 99%